Lisa and Lottie - Kastner, Erich 1899-1974.; De Larrea, Victoria (New York Knopf, 1969)
When they meet for the first time at summer camp, two ten-year-old girls discover they are twins and plot to bring their divorced parents together again.
Trans. of "Das doppelte Lottchen."
Keywords: Family life -- Fiction